The Effect of Multiple Role Conflict and Work Stress on Female Employee Performance with Work Motivation as a Mediator - Murni Nawungkrida; Dion Wahyudi; Arum Ambianasari (CV. Syntax Corporation Indonesia, 2024)
Female employees often face unique challenges in the workplace, especially when they have dual roles as workers and housekeepers. Dual role conflict can cause work stress, which impacts their performance at work. This study aims to analyze the effect of dual role conflict and work stress on the performance of female employees with work motivation as a mediator. This study uses a quantitative research method. The data collection method used in this study is to reveal the research variables using a scale. The data analysis method used in this study uses the help of the JASP Statistics application. The results of the study showed that there was a significant effect of dual role conflict on the performance of female employees. In addition, this study also showed that work stress had a significant effect on the performance of female employees in the educational institution. Furthermore, work motivation was proven to have an effect on the performance of female employees at YSM. This study revealed that dual role conflict affected the performance of female employees with work motivation as a mediator, and work stress also affected the performance of female employees with work motivation functioning as a mediator. The implications of this study indicate the importance of management paying attention to dual role conflict and job stress to improve the performance of female employees. In addition, the results of this study can serve as a basis for organizations in designing support programs that can increase work motivation and employee well-being.